Unresolved Issues in RNA Therapeutics in Vascular Diseases With a Focus on Aneurysm Disease - Schellinger, Isabel N.; Dannert, Angelika R.; Mattern, Karin; Raaz, Uwe; Tsao, Philip S. (Frontiers in Cardiovascular Medicine, 2021)
New technologies have greatly shaped the scientific and medical landscape within the last years. The unprecedented expansion of data and information on RNA biology has led to the discovery of new RNA classes with unique functions and unexpected modifications. Today, the biggest challenge is to transfer the large number of findings in basic RNA biology into corresponding clinical RNA-based therapeutics. Lately, this research begins to yield positive outcomes. RNA drugs advance to the final phases of clinical trials or even receive FDA approval. Furthermore, the introduction of the RNA-guided gene-editing technology CRISPR and advances in the delivery of messenger RNAs have triggered a major progression in the field of RNA-therapeutics. Especially short interfering RNAs and antisense oligonucleotides are promising examples for novel categories of therapeutics. However, several issues need to be addressed including intracellular delivery, toxicity and immune responses before utilizing RNAs in a clinical setting. In this review, we provide an overview on opportunities and challenges for clinical translation of RNA-based therapeutics, with an emphasis on advances in novel delivery technologies and abdominal aortic aneurysm disease where non-coding RNAs have been shown to play a crucial regulatory role.